The magnitude of a mid-Holocene sea-level highstand in the Strait of Makassar - Mann T.; Rovere A.; Schone T.; Klicpera A.; Stocchi P.; Lukman M.; Westphal H. (Geomorphology, 2016)
Knowledge on the timing and magnitude of past sea-level changes is essential to understand modern and future sea-level variability. Holocene sea-level data from literature on the west coast of Sulawesi, central Indonesia, suggest that this region experienced two relative sea-level highstands over the last 6000 years, with magnitudes exceeding two meters. However, recent datasets from the Indo-Pacific region do not support high-magnitude sea-level oscillations during the Holocene in tectonically stable far-field locations. Here we present a new, high-precision, mid-Holocene sea-level dataset from the Spermonde Shelf off southwest Sulawesi. We surveyed 21 fossil microatolls on the reef flats of two coral islands (Pulau Panambungan and Pulau Barrang Lompo) and referred their elevations to local mean sea level and to the height of living coral. Radiometrically calibrated ages from emergent fossil microatolls on Pulau Panambungan indicate a relative sea-level highstand not exceeding 0.5 m above present at ca. 5600 cal. yr BP. The highstand is followed by a relatively rapid sea-level fall towards present sea level that was reached at around 4000 cal. yr BP. Fossil microatolls from nearby Pulau Barrang Lompo show the same trend, however with a coherent negative vertical offset of about 0.8 m compared to their equivalents on Pulau Panambungan. The largely consistent gradients of both trends (-0.14 mm yr-1), the consistent elevation of living microatolls in the Spermonde, and a number of instructive geomorphic features indicate a localized, post-formational and probably recent drop of the fossil microatolls on the densely populated island Pulau Barrang Lompo. The relative sea-level trend inferred from Pulau Panambungan is well within the range of geophysical predictions based on ANICE-SELEN ice sheet model, which predict a highstand that is significantly lower than those predicted by other GIA models for this area. Although a complete interpretation of the Holocene sea-level history will require additional ...